Relative wages and pupil performance, evidence from TIMSS - Joshua Fullard (University of Essex, Institute for Social and Economic Research (ISER), 2021)
While it is widely established that higher wages attract more productive individuals into teaching, it is unclear if salaries can be used to motivate existing teachers to work harder, or more productively, in any way that affects pupil outcomes. Using teachers' predicted relative wages, calculated using a novel method of estimating teachers' outside option, we provide evidence that teachers do respond to higher wages and this improves pupil outcomes. Consistent with the predictions of the efficiency wage model a 10% increase in teachers' relative wages improves pupil performance in Science by 0.03sd, Math by 0.024sd as well as their enjoyment of learning by 0.05sd. The magnitude of these effects are similar to a 1 student reduction in class size or an additional hours of weekly tuition.
Keywords: I12; J31; J45; 330; Teacher Pay; School Productivity; Efficiency Wage